Emissions of carbon monoxide and dioxide from decomposing grass clippings – case study of football turfs - Sobol, Łukasz; Koziel, Jacek A.; Stegenta-Dąbrowska, Sylwia (Frontiers in Environmental Science, 2025)
Sports turfs and urban landscapes generate waste biomass in the form of grass clippings. Decomposing grass clippings can recycle nutrients to soil. However, decomposing can have adverse environmental effects such as gaseous emissions. The magnitude of air pollution caused by gaseous emissions from grass clippings is unknown. This research investigated CO, CO2, and O2 exchange during the decomposition of grass clippings. Emissions from grass clippings collected at four football fields with different levels of fertilization and agrotechnical treatments were studied. The mowed grass was collected throughout the spring-to-autumn football season. The results showed that grass clippings from sports turfs can generate up to 5 times more CO emissions compared to a mixture of grass and cattle manure. CO2 production and O2 consumption were relatively similar for all seasons, except for clippings from the unfertilized pitch. Artificial neural network (ANN) models predicted the CO and CO2 emissions resulting from the disposal of grass clippings with R2 for CO > 0.81 and CO2 > 0.98, respectively. This research contributes to emission inventories and highlights the relatively minor contribution from decomposing biomass.